Exploring new barriers to the implementation of frugal innovation projects among Spanish NGDOs - Delfa Rodríguez, Beatriz; Gomez, Georgina M.; Ballesteros, Carlos (Quaestiones Geographicae, 2025)
The concept of frugal innovation has attracted significant academic interest over the last decade, but its diffusion among non-governmental organisations (NGOs) with technology transfer programmes in the Global South has been insufficiently examined. This is despite the intuitive benefits these organisations could derive from simplicity, cost reduction and a human-centred approach related to frugal innovations. This research addresses that gap through a multiple-case study of innovation projects implemented by a Spanish NGO across three Latin American countries: Bolivia, Honduras, and Peru. The study first assesses the degree of frugality in these projects and subsequently focuses on the dissemination of frugal innovations, as well as the challenges encountered during project implementation in the field. Our findings indicate that core frugal attributes, such as simplicity and a human-centred approach, face fewer implementation hurdles and tend to facilitate project success. Nevertheless, the results reveal a mismatch between the envisioned ex ante frugality levels and those observed ex post in interviews with end-users and other agents after implementation. This research identifies the frugal innovation characteristics that contribute to improved project management and implementation success, as well as the implementation barriers that persist or emerge unexpectedly during the diffusion of frugal innovation. These include institutional misalignments, limited local ownership, and insufficient consideration of end-user practices.